Colorectal Cancer: From Pathophysiology to Novel Therapeutic Approaches - Valeria Barresi (Biomedicines, 2021)
According to the Global Cancer Statistics 2020, colorectal cancer (CRC) represents the third most frequent malignancy worldwide, and is the second in terms of mortality [...]